Does foreign direct investment stimulate the output growth of the formal economic sector in Vietnam: a subnational-level analysis - Thi Bich Thuy, Dao (Emerald Publishing Limited, 2022)
This study focuses on the relationship between foreign direct investment (FDI) and economic growth of the formal sector comprising all foreign and domestic registered enterprises engaged in production of goods and services.